Long-term consequences of an innovative redundancy-retraining project: The Austrian Steel Foundation - Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2000)
In the late 1980s privatization and down-sizing of nationalized steel mills and related firms in the metal industry have lead to large-scale redundancy plans. A special Steel Foundation was created as part of a social plan. This foundation acted like an independent training center, where displaced workers would spend relatively long training periods (sometimes several years), obtaining personality and orientation training, as well as formal education. The last step of the integrative program was placement assistance as well as assistance for creating one's own business. The foundation was financed by (higher) contributions from unemployment insurance funds, by the previous firms themselves, as well as by a collectively-bargained special tax on the remaining workers in the steel firms. Moreover the trainees themselves would have to support the foundation by giving up the interest accruing to their redundancy payments. I use combined data from Austrian social security records and from the Employment Service to look at participation decisions and on post-foundation economic performance, i.e. days worked and wage growth. As a control group I take all displaced workers from the firms who formed the foundation, using Instrumental Variables to solve the selection problem. The results show considerable wage gains - even for a period of five years after leaving the Foundation - as well as improved employment prospects. Finally, a cost-benefit analysis is performed to assess the long-term success of the Foundation.
Keywords: H43; I21; J53; J65; J58; 330; labor market programs; evaluation; cost-benefit analysis; instrumental variables; Stahlindustrie; Sozialplan; Umschulung; Arbeitsmarktpolitik; Kosten-Nutzen-Analyse; Österreich; Personalabbau; Berufliche Integration